1990
DOI: 10.1007/bf00120527
|View full text |Cite
|
Sign up to set email alerts
|

A wind tunnel study of turbulent flow over a two-dimensional ridge

Abstract: We present a wind-tunnel simulation of adiabatic atqospheric flow normal to a rough, twodimensional ridge. The data are analyzed in physical streamline coordinates, which are described in some detail. The mean velocity speed-up on the hill top is adequately predicted by existing formulae while the behaviour of the wake flow fits into a pattern that emerges from other wind-tunnel experiments. The turbulent stresses evolve in response to the extra strain rates induced by the hill, streamline curvature and accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
84
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 42 publications
16
84
0
Order By: Relevance
“…There is thus very little detailed data available on the way on which the hill affects the characteristics of the upstream flow. However, the experiments of Finnigan et al (1990) showed that at the upstream edge of an isolated hill of height 0.1δ the velocity 'speed-down' at z/H = 0.1 (with H here equal to the hill height) was about 13%, similar to the levels of speed-up seen for the valleys discussed here.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…There is thus very little detailed data available on the way on which the hill affects the characteristics of the upstream flow. However, the experiments of Finnigan et al (1990) showed that at the upstream edge of an isolated hill of height 0.1δ the velocity 'speed-down' at z/H = 0.1 (with H here equal to the hill height) was about 13%, similar to the levels of speed-up seen for the valleys discussed here.…”
Section: Resultssupporting
confidence: 75%
“…The perturbation pressure field will undoubtedly extend upstream so one expects to see an increase in near surface velocities upstream of the valley. The effects are illustrated by the 'inverse' case of flow over an isolated hill, as discussed by Finnigan et al (1990), for example, who show an increase in surface pressure as the hill is approached (see below). For steeper hills or valleys, but still not steep enough (for the valley case) to promote separation, the effect will be greater.…”
Section: Resultsmentioning
confidence: 99%
“…3. The agreement is only acceptable for the BR(max), BR(min), Black Mountain and Finnigan et al (1990) wind tunnel data. Mickle et al (1988), Beljaars and Taylor (1989) and Taylor and Walmsley (1996) has come up with this same conclusion, except for the wind tunnel data, which was not included in their works.…”
Section: Comparison With Observational Datamentioning
confidence: 91%
“…Kaimal and Finnigan (1994) point out that, as a hill is scaled down to fit into a wind tunnel, the surface roughness (grass, heather, stones) usually shrinks too much to satisfy the aerodynamically fully rough condition that ensure flow similarity. This fact, widely recognized in the literature (Britter et al, 1981;Gong and Ibbetson, 1989;Finnigan et al, 1990), reduces the applicability of such measurements. As Athanassiadou and Castro (2001) observe, 'Laboratory experiments … concentrate on flow that is not always fully rough and, as a result, not directly applicable to the atmosphere.'…”
Section: Comparison With Observational Datamentioning
confidence: 98%
See 1 more Smart Citation